Loss of Secreted Frizzled-Related Protein-1 Leads to Deterioration of Cardiac Function in Mice and Plays a Role in Human Cardiomyopathy. (March 2015) - Sklepkiewicz, Piotr; Shiomi, Takayuki; Kaur, Rajbir; Sun, Jie; Kwon, Susan; Mercer, Becky; Bodine, Peter; Schermuly, Ralph Theo; George, Isaac; Schulze, P. Christian; D'Armiento, Jeanine M.
Abstract : Background—: The Wnt/β-catenin signaling pathway plays a central role during cardiac development and has been implicated in cardiac remodeling and aging. However, the role of Wnt modulators in this process is unknown. In this study, we examined the role of the Wnt signaling inhibitor secreted frizzled-related protein-1 (sFRP-1) in aged wild-type and sFRP-1–deficient mice. Methods and Results—: sFRP-1 gene deletion mice were grossly normal with no difference in mortality but developed abnormal cardiac structure and dysfunction with progressive age. Ventricular dilation and hypertrophy in addition to deterioration of cardiac function and massive cardiac fibrosis, all features present in dilated cardiomyopathy, were observed in the aged sFRP-1 knockout mice. Loss of sFRP-1 led to increased expression of Wnt ligands (Wnt1, 3, 7b, and 16) and Wnt target genes (Wisp1 and Lef1) in aged hearts, which correlated with increased protein levels of β-catenin. Cardiac fibroblasts lacking endogenous sFRP-1 showed increased α-smooth muscle actin expression, higher cell proliferation rates, and increased collagen production consistent with the cardiac phenotype exhibited in aged sFRP-1 knockout mice. The clinical relevance of these findings was supported by the demonstration of decreased sFRP-1 gene expression and increased Wisp-1 levels in the left ventricles of patients with ischemic dilated cardiomyopathy and dilated cardiomyopathy. Conclusions—: This study identifies a novel role of sFRP-1 in age-related cardiac deterioration and fibrosis. Further exploration of this pathway will identify downstream molecules important in these processes and also suggest the potential use of Wnt signaling agents as therapeutic targets for age-related cardiovascular disorders in humans.